INCORPORATION OF ZIRCONOCENE INTO N-PHTHALOYL AMINO ACIDS AND KETOXIMES: OPTIMIZED STRUCTURE OF C26 H28 N2 O5 Zr AND OPTIMIZED ENERGY BASED ON COMPUTATIONAL ANALYSIS - Kanika Sharma; Suchitra Budania; Sanjiv Saxena; Asha Jain (International Journal of Innovations in Engineering Research and Technology, 2022)
Incorporation of zirconocene into N-phthaloyl amino acids and ketooximes was accomplished by the reaction of zirconocene dichloride with these two ligands in the presence of triethylamine in 1:1:1:2 molar ratios in refluxing dry THF. This interaction afforded solid products of the type Cp2ZrLA. A pentacoordinated geometry may be assigned to these complexes with the assistance of mass and spectroscopic studies. In these complexes, the coordination behavior of N-phthaloyl amino acids and ketoximes is bidentate and monodentate, respectively. The optimized structure, energy, geometry, energy gap and stability of one representative ziconocene complex were studied by using DFT(B3LYP) to corroborate the structures of these products.